Faktor yang menggalakkan penglibatan siswi di dalam sukan wanita: satu tinjauan kualitatif - Mohamed, Ani Mazlina Dewi; Abdul Latif, Rozita; Kada, Lily; Omar Fauzee, Mohd Sofian; Jamalis, Marjohan (Asian Centre for Research on University Learning and Teaching (ACRULeT), Faculty of Education, Universiti Teknologi MARA, 2008)
The objective of this research is to identify factors that influence the involvement of female university students in sports. Ten university students who were involved in the National Women’s Sports 2007 agreed to be interviewed. These respondents agreed to be tape-recorded during the data collection for this research. All recording were transcribed and analyzed thematically. The three main themes that emerged from the analysis were: involvement in sports, intrapersonal and interpersonal aspects. The findings show that excitement was the main factor for the female students’ involvement in sports. The recommendations and other findings are also discussed in this research.